Economic burden of gastrointestinal cancer under the protection of the New Rural Cooperative Medical Scheme in a region of rural China with high incidence of oesophageal cancer: cross‐sectional survey. Issue 7 (25th May 2016) - Li, Xiang; Cai, Hong; Wang, Chaoyi; Guo, Chuanhai; He, Zhonghu; Ke, Yang
Abstract: Objective: To evaluate the financial burden of oesophageal cancer under the protection of the new Rural Cooperative Medical Scheme (NCMS) and to provide evidence and suggestions to policymakers in a high‐incidence region in China. Methods: We analysed inpatient claim data for oesophageal cancer, gastric cancer and colorectal cancer from 1 January to 31 December 2013. The data were extracted from the NCMS management system of Hua County, Henan Province, a typical high‐risk region for oesophageal cancer in China. Cancer‐specific health economic indicators were calculated to evaluate the financial burden under the protection of the local NCMS. Results: The total cost of oesophageal cancer was 2.7–3.6 times higher than that of gastric cancer and colorectal cancer, respectively, due to high incidence of oesophageal cancer. For each hospitalisation to treat oesophageal cancer, the average total cost and out‐of‐pocket expenses after reimbursement equalled an entire year's gross domestic product per capita and per capita disposable income, respectively, for the local area. The average total cost per hospitalisation for oesophageal cancer increased monotonically with hospital level for surgical hospitalisations, and it increased more rapidly for non‐surgical hospitalisations (from $301 to $2589, 860%) than for gastric cancer (from $289 to $1453, 503%) and colorectal cancer (from $359 to $1610, 448%). Vulnerable groups with less access to high‐level hospitals were found in different gender and age groups. Conclusions: Oesophageal cancer imposes serious financial burdens on communities and patients' households in this high‐incidence region, and no preferential policy from the local NCMS has been designed to address this issue. A special supportive policy should be developed on the basis of local disease profiles and population characteristics to alleviate the financial burden of populations at high risk for certain high‐cost diseases.